(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
The article describes the botanical and morphological characteristics of Curcuma longa L. (turmeric), its phytochemical composition (curcuminoids, essential oils), pharmacological effects ( anti -inflammatory , antioxidant, metabolic, neuroprotective, antimicrobial) , and clinical evidence seeing was published . The literature search covered the period 2000–2024 and selected systematic reviews, in vitro/in vivo experiments, and clinical trials. The results highlighted the modulation of NF-κB, COX-2, Nrf2 pathways by curcuminoids, bioavailability issues, and strategies to address them (piperine, phytosomes, nanoformulations). There is evidence of symptomatic relief in osteoarthritis, metabolic syndrome, and respiratory diseases, but evaluation is limited due to the diversity of doses, formulations, and designs. In conclusion, although the safety of turmeric is good, the need for standardization, increased bioavailability, and high-quality clinical trials is emphasized.